1959
DOI: 10.1508/cytologia.24.149
|View full text |Cite
|
Sign up to set email alerts
|

Cyto-genetics of Millets (2)

Abstract: Discussions Secondary AssociationThe association of bivalents at meiosis was first observed by Kuwada (1910) in Oryza sativa only in second metaphase. Ishikawa (1911) found secondary pairing also at first metaphase of Dahlia variabilis . Since then various authors have found this phenomenon in different genera. Darlington (1928) originally advocated the theory of secondary pairing in his studies on Prunus. It was put on a systematic basis by Lawrence (1931) who has discussed all the known cases of secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Lysov (1975) also referred to some tetraploid plants (2n = 72) that have bigger panicles and seeds but, surprisingly, lower productivity. Chandola (1959b) found that proso millet can produce uni-and multivalents at meiosis and thought it quite likely that tetraploids of P. miliaceum originated through autopolyploidy. Hunt et al (2014) described the 2n = 4x = 36 chromosomes as small, varying from 2.2 to 6.0 μm in length at metaphase (see also section 6).…”
Section: Description and Account Of Variationmentioning
confidence: 99%
“…Lysov (1975) also referred to some tetraploid plants (2n = 72) that have bigger panicles and seeds but, surprisingly, lower productivity. Chandola (1959b) found that proso millet can produce uni-and multivalents at meiosis and thought it quite likely that tetraploids of P. miliaceum originated through autopolyploidy. Hunt et al (2014) described the 2n = 4x = 36 chromosomes as small, varying from 2.2 to 6.0 μm in length at metaphase (see also section 6).…”
Section: Description and Account Of Variationmentioning
confidence: 99%